PENGEMBANGAN KURIKULUM PROGRAM STUDI PENDIDIKAN AGAMA ISLAM MELALUI TRACER STUDY ALUMNI - Muhammad Arifin Rahmanto; Shobah Shofariyani Iryanti; Lismawati (Jurnal Pendidikan Islam, 2021)
The research objective of PAI UHAMKA tracer study is to determine the quality of graduates and the demands of the world of work. This research is a descriptive quantitative research through a survey approach which includes three stages: 1) developing concepts and instruments; 2) data collection and 3) data analysis. The research samples were graduates of PAI UHAMKA 2017. For the data analysis stage, a mix method was used with the Sequential Explanatory model. The results showed that the majority of PAI UHAMKA graduates in 2017 were absorbed in working in the government and private sectors. The competencies possessed by graduates are in accordance with the job. The assessment of graduate respondents on the learning process states that the learning methods, qualifications of teaching staff and learning facilities are appropriate to support the increase in knowledge and abilities needed to support work, and the guidance of AIK has an impact on the worship obedience of graduates.